Comment on "Atomic structure calculations for F-like tungsten" by S. Aggarwal [Chin. Phys B 23 (2014) 093203]. (20th February 2016) - Aggarwal, Kanti M
Abstract: Recently, S. Aggarwal [ Chin. Phys. B 23 (2014) 093203] reported energy levels, radiative rates, and the lifetimes for the lowest 60 levels belonging to the 2s 2 2p 5, 2s2p 6, and 2s 2 2p 4 3 ℓ configurations of F-like tungsten. There is no discrepancy for his calculated energies for the levels and the radiative rates for the limited number of E1 transitions, but the reported results for the lifetimes are highly inaccurate. According to our calculations, errors in his reported lifetimes are up to 6 orders of magnitude for several levels. Here we report the correct lifetimes for future comparisons and applications, and also explain the reason for the discrepancies.